2016
DOI: 10.4103/1319-2442.185241
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge, awareness, and acceptability of renal transplantation among patients with end-stage renal disease in Ibadan, Nigeria

Abstract: Renal transplantation is well established in the USA, Europe, India, and South Africa. However, it is still in its infancy in Nigeria. The objective of our study is to determine the knowledge, awareness, and acceptability of renal transplant among patients with end-stage renal disease (ESRD) and the factors which are responsible for the low level of transplantation in Ibadan, Nigeria. A 15-item pilot-tested questionnaire was administered to willing patients with ESRD seen at the medical outpatient clinic of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…The proportion our CKD population willing to accept kidney transplantation is similar to study ndings by Alansari et al among haemodialysis patients in Saudi Arabia 67.3% vs 69%) (10). Similarly, a Nigerian study among ESRD patients showed that 66.7% were willing to accept kidney transplantation (11). In contrast, the proportion willing to accept kidney transplantation in a study by Ilori et al among African American population was lower.…”
Section: Discussionsupporting
confidence: 84%
“…The proportion our CKD population willing to accept kidney transplantation is similar to study ndings by Alansari et al among haemodialysis patients in Saudi Arabia 67.3% vs 69%) (10). Similarly, a Nigerian study among ESRD patients showed that 66.7% were willing to accept kidney transplantation (11). In contrast, the proportion willing to accept kidney transplantation in a study by Ilori et al among African American population was lower.…”
Section: Discussionsupporting
confidence: 84%
“…The Cochran’s formula was used to calculate a minimum sample size of 342 participants for the study ( n = minimum required sample size; α = Significance level = 5%; = z-score at 95% confidence level = 1.96; p = proportion of patients willing to accept kidney transplant which was 66.7% [ 13 ] and e = margin of error = 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…[1] Our study shows that the understanding about renal transplantation was very poor in Indian maintenance hemodialysis patients. Sadly only 72% of our patients had knowledge about transplant as a modality for renal replacement therapy, lesser than the West-African MHD patients from Cote d'Ivoire (97.3%) and Nigeria (75%), [4,5] however they were better informed than the Saudi Arabian (39%) and Bangladesh CKD cohorts (30%, 34%). [6][7][8] Consequently lesser number of our patients (69.4%) were willing for transplant than the Cote d'Ivoire cohort (78.3%), [4] Saudi-Arabians had comparable willingness (69%) as they also feared their old age (61%) and surgical complications (26%), whereas Chinese feared transplantation the most with only 46.4% willing for transplant.…”
Section: Discussionmentioning
confidence: 76%
“…[4] The concern about high cost of transplant compared to hemodialysis, were common to many. [4,5] Another common deterring factor in our study as well as in worldwide meta-analysis, [11] was the concern for family donor's health, whereas many of these wished to undergo transplantation if deceased donor kidney was available. Unfortunately deceased donor program has not yet kick-started in our state, and we refer our patients to get enrolled at a nearby union territory central government premium institute, where the whole process is very lengthy and painstaking, and consequently only 11% of our patients were enrolled for the same, and these too were on waiting list for years.…”
Section: Discussionmentioning
confidence: 82%